Louise Pound : scholar, athlete, feminist pioneer - Cochran, Robert, 1943- (Book collections on Project MUSE., 2009)
Louise Pound (1872?1958) was a distinguished literary scholar, renowned athlete, accomplished musician, and devoted women?s sports advocate. She is perhaps best remembered for her groundbreaking work in the field of linguistics and folklore and for her role as the first woman president of the Modern Language Association. A member of a distinguished Nebraska family that included her brother, the prominent legal scholar Roscoe Pound, Louise completed her undergraduate education at the University of Nebraska. When American universities wouldn?t admit her for graduate study, she went on to obtain.